PENGARUH OBESITAS TERHADAP KARAKTERISTIK POLA BERJALAN : LITERATURE REVIEW - Wahyu Prasasti Mutiadesi Mintardjono; Wardiansah Wardiansah; Hartanto Hartanto (Fakultas Kedokteran, Universitas Hang Tuah, 2023)
Obesity is a global health problem with increasing prevalence worldwide. One aspect of concern is how obesity can affect an individual's gait characteristics, leading to musculoskeletal disorders. Numerous studies have explored the gait characteristics experienced by individuals with obesity. The objective of this literature review is to provide further information on the gait characteristics of individuals with obesity, which can be utilized for the prevention of obesity-related musculoskeletal disorders. The methodology employed in this study is a literature review, creating conclusions from selected data sources from various national and international journals published between 2011 and 2021. The findings reveal that obesity can lead to decreased balance, reduced walking speed, and influence several gait characteristic parameters, such as changes in step length and width, stride length, as well as various angles formed by the knee and ankle joints during walking, resulting in a distinct gait pattern compared to normal gait. Therefore, it can be concluded that individuals with obesity are prone to exhibit an altered gait pattern, which can potentially contribute to musculoskeletal problems such as osteoarthritis.